Exploring visual scenarios as an aspect-oriented modeling language - Asteasuain, Fernando (2010)
Very well known problems such as the fragility problem, the AOP paradox, or the aspect interference problem threaten aspect oriented application in the modeling phase. In this work we explore FVS, a declarative visual language, as an aspect-oriented modeling language. Our language exhibits a very flexible and rich joinpoint model to leverage aspect-oriented application and is suitable for incremental modeling, a highly desirable quality attribute in any modeling language.